Net neutrality and consumer welfare: divergent approaches to the Egyptian telecommunication regulation - Hamada, Mennatullah Helmy (AUC Knowledge Fountain, 2020)
This thesis explores the implications of the debate on net neutrality on telecommunication policy in Egypt. I argue that consumer welfare should be the main determining factor of the effects of net neutrality obligations on the telecom sector. Consumer welfare must remain the focus of any regulator while applying net neutrality obligations. Consumers in any telecom market care about three elements, namely, prices, quality and speed of the internet, and openness and accessibility of the content available over the internet. Meanwhile, the main controllers of the telecom market are torn between preserving the nature of the internet and their own best interests. Since, the Egyptian telecom market has its unique structure and main key players, this paper proposes an implementation strategy for net neutrality obligations to be met in the Egyptian market for the consumers best interests.